1997
DOI: 10.1046/j.1365-2141.1997.d01-2011.x
|View full text |Cite
|
Sign up to set email alerts
|

analysis of CD9, CD32 and p67 signalling: use of degranulated platelets indicates direct involvement of CD9 and p67 in integrin activation

Abstract: Summary. The use of agonist monoclonal antibodies (mAbs) to probe the signalling function of platelet membrane proteins is severely limited by the dependence of the mAb effect on Fc-FcgRII interaction. Furthermore, in addition to its anchoring role, the FcgRII receptor itself generates a stimulation signal resulting in granule secretion. Platelet stimulation by the released granule contents can then further obscure the original activation signal. Here we demonstrate that these problems are largely overcome by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Other studies showed that anti-CD9 mAbs caused a rise in intracellular calcium and enhanced tyrosine phosphorylation in platelets and Schwann cells (Favier et al, 1989;Yatomi et al, 1993;Hadjiargyrou and Patterson et al, 1995). In platelets, intracytoplasmic signalling pathways mimic those caused by integrin β 3 (gpIIb/IIIa), suggesting that CD9 has a role in integrin-associated cell signalling (Slupsky et al, 1989(Slupsky et al, , 1997. We also observed that anti-CD9 mAb (ALB6) enhanced migration of a human choriocarcinoma-derived cell line, BeWo cells, and that integrin α 5 β 1 is involved in the effect of the anti-CD9 mAb on BeWo cell migration (Hirano et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that anti-CD9 mAbs caused a rise in intracellular calcium and enhanced tyrosine phosphorylation in platelets and Schwann cells (Favier et al, 1989;Yatomi et al, 1993;Hadjiargyrou and Patterson et al, 1995). In platelets, intracytoplasmic signalling pathways mimic those caused by integrin β 3 (gpIIb/IIIa), suggesting that CD9 has a role in integrin-associated cell signalling (Slupsky et al, 1989(Slupsky et al, , 1997. We also observed that anti-CD9 mAb (ALB6) enhanced migration of a human choriocarcinoma-derived cell line, BeWo cells, and that integrin α 5 β 1 is involved in the effect of the anti-CD9 mAb on BeWo cell migration (Hirano et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…14 Our data raise the possibility that signal transduction by CD36 may involve CD9 and protein kinase C. Platelets exhibit similar responses to anti-CD36 and anti-CD9 antibodies. 23,41,42 Both antibodies activate ␣IIb␤3 to bind fibrinogen and cause platelet aggregation. Platelet aggregation that is induced by an antibody to either antigen is inhibited by protein kinase C inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…15,62 Expression of CD9 in a human B-cell line increases the tyrosine phosphorylation of 69-and 130-kDa bands in cells adhering to FN, 9 whereas in Schwann cells, anti-CD9 mAbs enhance the tyrosine phosphorylation of 8-to 220-kDa proteins. 5 In the experimental conditions under which we observed inhibition of lesion repair, ALMA.1 did not modify the tyrosine phosphorylation profile of ECs over a period of 48 hours, even in the presence of a phosphatase inhibitor, to reveal low phosphorylation levels, nor did clustering of CD9 modify this profile (data not shown).…”
Section: Fakmentioning
confidence: 99%